Bridging the gap: an examination of teacher deployment in Cambodian preschools - Phal Chea; Kexin Wang; Keiichi Ogawa; Akemi Ashida (International Journal of Child Care and Education Policy)
Abstract The current study examines teacher deployment strategies in Cambodian preschools and identifies challenges related to the supply and deployment of teaching staff in early childhood education by assessing the adequacy, efficiency, and quality of teacher deployment. This study employs multiple approaches in data collection, including desk review of existing policies and literature, analysis of school-level administrative data, and in-depth interviews at the national, sub-national, and school levels. The findings from the study highlight the severe teacher shortage, uneven distribution of qualified teachers and disparities in teacher quality in Cambodian early childhood education. Newly graduated and well-trained preschool teachers are disproportionately deployed in urban areas, while preschool teachers in rural schools are not adequately trained to be preschool teachers. Existing efforts to expand preschool access are insufficient without simultaneously addressing the urgent need for properly trained preschool teachers. Based on these findings, the study offers policy recommendations, including scaling up pre-service training, strengthening teacher workforce planning through improved data systems, and implementing targeted incentives to ensure a more equitable and sustainable ECE teacher workforce.